Optimization of ATP Synthase c–Rings for Oxygenic Photosynthesis - Davis, Geoffry A.; Kramer, David M. (Frontiers in Plant Science, 2020)
The conversion of sunlight into useable cellular energy occurs via the proton–coupled electron transfer reactions of photosynthesis. Light is absorbed by photosynthetic pigments and transferred to photochemical reaction centers to initiate electron and proton transfer reactions to store energy in a redox gradient and an electrochemical proton gradient (proton motive force, pmf), composed of a concentration gradient (pH) and an electric field (ψ), which drives the synthesis of ATP through the thylakoid FoF1-ATP synthase. Although ATP synthase structure and function are conserved across biological kingdoms, the number of membrane–embedded ion–binding c subunits varies between organisms, ranging from 8–17, theoretically altering the H+/ATP ratio for different ATP synthase complexes, with profound implications for the bioenergetic processes of cellular metabolism. Of the known c–ring stoichiometries, photosynthetic c–rings are among the largest identified stoichiometries, and it has been proposed that decreasing the c-stoichiometry could increase the energy conversion efficiency of photosynthesis. Indeed, there is strong evidence that the high H+/ATP of the chloroplast ATP synthase results in a low ATP/NADPH ratio produced by photosynthetic linear electron flow, requiring secondary processes such as cyclic electron flow to support downstream metabolism. We hypothesize that the larger c subunit stoichiometry observed in photosynthetic ATP synthases was selected for because it allows the thylakoid to maintain pmf in a range where ATP synthesis is supported, but avoids excess ψ and pH, both of which can lead to production of reactive oxygen species and subsequent photodamage. Numerical kinetic simulations of the energetics of chloroplast photosynthetic reactions with altered c–ring size predicts the energy storage of pmf and its effects on the photochemical reaction centers strongly support this hypothesis, suggesting that, despite the low efficiency and suboptimal ATP/NADPH ratio, a high H+/ATP is favored to avoid photodamage. This has important implications for the evolution and regulation of photosynthesis as well as for synthetic biology efforts to alter photosynthetic efficiency by engineering the ATP synthase.